Hubungan Antara Ilmu Pengetahuan dan Teknologi (IPTEK) dengan Pendidikan Islam : Tantangan dan Peluang - Kokom Komariah; Andriyani; Dede Rosyada; Nurmalia Lusida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of the research is to find out how Islamic education is related to science and technology (IPTEK). Science and Technology provides a strong knowledge base for understanding the universe and developing technology that is beneficial to humans. In contrast, Islamic education instills moral, ethical and spiritual principles that shape an individual's personality. Apart from that, schools teach the use of science and technology in accordance with religious beliefs. The aim of this research is to show how these two fields work together and benefit each other. The integration of science and technology (IPTEK) with Islamic education offers various significant opportunities to improve the quality of education, research, as well as creating sustainable solutions and building strong character. The use of modern technology in the learning process can enrich learning material, make it more interactive, and provide access to a wider range of educational resources. In addition, research based on Islamic ethical principles ensures that technological innovation is not only oriented towards economic benefits but also takes into account human and moral values. Therefore, the integration of science and technology and Islamic education allows for a balanced education system where technological and scientific progress can be balanced with the application of moral and ethical values. This will produce students who can make positive contributions to society and their environment.